ST. THEODOSIUS PASSION. HOW AND WHY TH.G. DOBZHANSKY BECАME A NON-RETURNER - M. B. Konashev (Вавиловский журнал генетики и селекции)
Within one year since May 1930 till August 1931 Th. Dobzhansky undertook an intership in the USA on a scholarship from the International Education Board (The Rockefeller Foundation). His preparation for returning to the USSR included all necessary actions for getting a new job and prolongation of his and his wife’s passports. After receiving three letters from N.I. Vavilov, of June, 9, 11 and 12, 1931, Th. Dobzhansky decided to stay in the USA and became an asylee (the Russian term “nevozvrashchenets” literally means non-returner). In 1932, at the 6th International Genetic Congress in Ithaca, USA, N.I. Vavilov said that Dobzhansky’s decision was sound.